Training on writing COVID-19 slogans for teens and basic food assistance for angkot drivers affected by the pandemic - Amalia, Nur; Nawawi, N.; Puspitasari , Nur Aini (Journal of Community Service and Empowerment, 2021)
Activities to implement one of the Tridharma Perguruan Tinggi to continue to share knowledge and share basic needs with communities affected by COVID-19 need to be done. This activity aims to provide training in writing COVID-19 slogans for adolescents and providing groceries for Ciputat-Parung Angkot Drivers who are affected by COVID-19. The activity was held in May 2020. The activity was carried out well and was welcomed by the community. This is evidenced by the enthusiasm of teenagers in writing COVID-19 slogans and being able to foster a spirit of creativity and productivity so that they can raise awareness of teenagers.